The challenge of decolonizing knowledge: the Marielle Franco Favela Dictionary - Sonia Fleury; Clara Polycarpo; Palloma Menezes; Marcelo Fornazin (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
Favelas are described by dominant groups in the society from negative stereotypes, nevertheless, they are now challenged by various collective actors. Departing from an endeavor gathering academics and dwellers, the Marielle Franco Favelas Dictionary is an online platform that, by means of collective knowledge building, aims to spread different narratives regarding these territories and their populations. This article interrogates how encounters and divergences between knowledge of academics, activists, and favelas' dwellers happened. By these means, we present the Dictionary trajectory that aims overcome tensions and thus incorporate other languages and registries able to accommodate favelas' production and memories.